Noise of hot carriers in single-injection solid-state diodes with traps lying below the Fermi level - Sharma Y.K. (My University, 2025)
An exact and an approximate solution for the current-voltage characteristics of the hot-carrier single-injection solid-state diodes with a single set of traps lying well below the thermal-equilibrium Fermi level (operating in the insulator regime) have been calculated. In addition, the low frequency and thermal noise are calculated at different critical currents. The approximate solution is calculated with the help of the regional approximation. An expression for the critical currents and voltages shows that there is a large change in current occuring over a restricted change in voltage. It appears from the study of the electrical-noise behavior that there is a noise-suppression effect at higher currents. © 1974 The American Physical Society.